Adding NBPT to urea increases N use efficiency of maize and decreases the abundance of N-cycling soil microbes under reduced fertilizer-N rate on the North China Plain. - Gaoyuan Liu; Zhanping Yang; Jun Du; Ailing He; Huanhuan Yang; Guangyuan Xue; Congwen Yu; Yuting Zhang (PLoS ONE, 2020)
Urease inhibitor (UI) and nitrification inhibitor (NI) can reduce N losses from agricultural soils but effects of inhibitors on N cycle are unclear. A field experiment was conducted with maize to test effects of UI (N-(n-Butyl) thiophosphoric, NBPT) and NI (3,4-dimethylepyrazolephosphate, DMPP) on N uptake and N-cycling soil microbes. Five treatments were imposed: no N fertilizer input (CK), conventional fertilization (CF) and 80% of urea input with NBPT (80%U+UI), with DMPP (80%U+NI) and with half NBPT and half DMPP (80%U+1/2(UI+NI)). There were no significant differences in biomass between 80%U+UI, 80%U+NI and CF but harvest index was increased under 80%U+UI and 80%U+NI. Compared to CF, N use efficiency of grain under 80%U+UI was increased by 7.1%, whereas grain yield and N uptake under 80%U+1/2(UI+NI) were decreased by 8.2% and 9.4%, respectively. The peak soil [Formula: see text] content was at about 15 days after fertilization (DAF) under CF but 30 DAF under the inhibitor treatments. In soils of 80%U+UI, the activities of urease and nitrate reductase were decreased between 15-45 DAF and between 5-30 DAF. The abundance of N-cycling soil microbes was affected: 80%U+UI and 80%U+NI reduced the copies of the amoA AOA and nir genes at about 15 days and reduced the copies of the amoA AOB gene at about 30 days. Correlation analysis indicated that there were significant positive relationships between amoA AOB gene and [Formula: see text], as well as between nirK gene and [Formula: see text]. Overall, urea applied with NBPT has greater potential for improving maize N use efficiency and inhibiting nitrification under reduced fertilizer-N applications.